Complete Genome Sequences of Walnut-Associated Xanthomonas euroxanthea Strains CPBF 367 and CPBF 426 Obtained by Illumina/Nanopore Hybrid Assembly - Teixeira, Miguel (Microbiol Resour Announc, 2020)
We present the complete genome sequences of two Xanthomonas euroxanthea strains isolated from buds of a walnut tree. The whole-genome sequences of strains CPBF 367 and CPBF 426 consist of two circular chromosomes of 4,923,218 bp and 4,883,254 bp and two putative plasmids of 45,241 bp and 17,394 bp, respectively. These data may contribute to the understanding of Xanthomonas species-specific adaptations to walnut.